Pengaruh Penggunaan Media Komik Digital Terhadap Peningkatan Aktivitas Belajar PAI Di SMP Negeri 10 Denpasar Tahun Pelajaran 2020/2021 - Maharani, Erfina; Soedjiwo, Novena Ade Fredyarini; Rusmayani, Rusmayani (Faidatuna, 2021)
Learning media in the form of comics can foster Islamic religious education learning activities in students, so that students are trained with the material taught by the teacher. Students become active and interested in learning in reading the material, students try to understand the material by studying the storyline that is made. The formulation of the research problem is; 1) is there any effect the use of digital comics media has on increasing PAI learning activities at SMP Negeri 10 Denpasar in the 2020/2021 academic year, and 2) how much is the contribution of using digital comics media to increasing PAI learning activities at SMP Negeri 10 Denpasar in the 2020/2021 academic year. This study aims to determine; 1) the influence of the use of digital comic media on increasing PAI learning activities at SMP Negeri 10 Denpasar in the 2020/2021 academic year, and 2) how much does the use of digital comics media contribute to increasing PAI learning activities at SMP Negeri 10 Denpasar in the 2020/2021 academic year. This study uses a quantitative approach and in determining the sample using a saturated sampling technique with the results of 79 populations. Data collection techniques using questionnaires and analysis techniques using Product Moment. The results showed that there were; 1) the effect of using digital comics media on increasing PAI learning activities at SMP Negeri 10 Denpasar for the 2020/2021 academic year has a moderate or sufficient positive impact, with the results of the correlation, it is known that rxy = 3.706 is greater than the value of thetable Product Moment r, both at a significant level 5 percent is 1.991, and 2) the coefficient of determination is 15.1%, while the remaining 84.9% is determined by other variables.